Phylogenomics - Bleidorn, Christoph (Springer, 2017)
All life on earth shares a common ancestor, and the aim of phylogenetic systematics is to reconstruct the tree or network of life. Shortly after the availability of the first protein sequences, molecular phylogenetic approaches were developed to understand the evolutionary relationships between proteins (or genes). It became clear that gene trees will also help to unravel the phylogeny of species. The introduction of Sanger sequencing and polymerase chain reaction (PCR) paved the way that genetic approaches became available across the scientific community and contributed to the rise of molecular phylogenetics. At the end of the 1990s, results from single-gene studies challenged the century-old textbook view of evolutionary relationships of many groups (e.g. animals, plants). Fierce discussions regarding the validity of these results led to important methodological advances, and, nowadays, molecular phylogenies are broadly accepted to represent organismal relationships in textbooks. In the mid-2000s, the way of sequencing has been revolutionized, leading to a huge drop in its costs, and unprecedented amounts of sequence data became affordable for every type of study and also for non-model organisms. This development transformed the field of molecular phylogenetics to phylogenomics, where genome-scale data (genomes, transcriptomes) can be exploited. The term phylogenomics was already coined in 1998 by Jonathan Eisen (also known under his twitter handle @phylogenomics), who outlined the importance of phylogenetic methods for the annotation of genes without relying on direct (time consuming) functional studies. This underlines how deeply embedded phylogenetic methods are in the field of genomics. The theoretical background for reconstructing gene trees (functional annotations) and species trees (reconstruction of the tree of life) is broadly overlapping. In this book I will introduce the major steps of phylogenomic analyses in general. The first two chapters briefly introduce the field of genomics (7 Chap. 1, «Genomes») and the evolution and peculiarities of organellar genomes (7 Chap. 2, «Organellar Genomes and Endosymbionts»). In 7 Chap. 3 («Sequencing Techniques»), I review the most widely used sequencing platforms, which is difficult in a print format, as the field advances so fast that many numbers describing the output of these machines might be already out of date when you read this chapter. 7 Chapter 4 («Sequencing Strategies») gives an overview of different strategies to sequence complete or partial genomes and transcriptomes. The outputs of every sequencing platform are sequences which are considerably shorter than chromosomes and in the case of short-read sequencing also shorter than most genes. In 7 Chap. 5 («Assembly and Data Quality»), ways to puzzle these small pieces into more complete representations of genomes and genes (called assembly) are introduced. Fundamental steps for every phylogenomic study are alignments, read mapping and finding homologous genes, which are explained in 7 Chaps. 6 («Alignment and Mapping») and 7 («Finding Genes»). Based on a sequence alignment, it is possible to reconstruct phylogenetic trees, and the methods are briefly reviewed in 7 Chap. 8 («Phylogenetic Analyses»). I kept this chapter on purpose rather brief, as many excellent textbooks describing these methods (and its underlying algorithms) in detail are available (see references in 7 Chap. 8).
An Introduction